Integrated Optical Frequency Comb Applied to 5G and Beyond - Lima , Eduardo Saia (2023)
This work is a partnership between National Institute of Telecommunications (Inatel) and Scuola Superiore Sant???Anna. The Indium Phosphide (InP) monolithically integrated optical frequency comb (OFC) based on cascaded phase modulators employed in this Thesis was developed by the Italian researchers and indeed characterized and applied to 5G communications in this work. The photonic integrated circuit (PIC) is broadly tunable in terms of OFC operating wavelength and frequency spacing, with footprint of around 4.5 ?? 2.5 mm2 . The compact device has been used for optically generating and distributing low-phase noise mm-waves signals by means of radiofrequency (RF) multiplication since the OFC lines share strong-phase correlation, potential to generate mm-wave based on the heterodyne detection. Phase noise measurements enable the precise characterization of the OFC-based mm-wave signals frequency stability. In particular, a tenfold multiplied signal (26 GHz) provided a remarkable low-phase-noise feature, equivalent to a commercially available RF generator used as a source at the same electrical power, i.e., -50 dBc/Hz and -80 dBc/Hz at 10 Hz and 1 kHz offset frequency, respectively. The proposed system also emonstrated frequency multiplication up to 12-times without phase noise increment, validating its use for mm-wave applications over a wide frequency range. Furthermore, a full 5G mm-waves demonstrator based on the PIC has been implemented. The PIC has been placed in a centralized radio access network (C-RAN) architecture, enabling the distribution of the generated OFC, aiming to support multiple OFC applications using a single device. Two low-phase noise mm-waves signals have been remotely generated by dividing and transmitting the original OFC in two distinct approaches: 12.5-km of single-mode fiber (SMF) fronthaul and a 12.5-km SMF midhaul, followed by a 10-m long free-space optics (FSO) fronthaul link. Finally, two 10-m reach 5G New Radio (NR) wireless access networks operating at 26 GHz assisted by the flexible OFC network have been reported within the 3rd Generation Partnership Project (3GPP) Release 15 requirements in terms of root mean square error vector magnitude EVMRMS), demonstrating the feasibility and potential of the integrated OFC technology for the 5G mm-waves access networks.